AB0746 High Prevalence of Cardiovascular Comorbidity in Patients with Psoriatic Arthritis and Moderate-To-Severy Plaque Psoriasis: A Retrospective Dermatological Clinic-Based Study. (15th July 2016) - Batkaeva, N.; Korotaeva, T.; Batkaev, E.
Abstract : Background: An association between inflammation, psoriasis (PsO), psoriatic arthritis (PsA) and increased cardiovascular comorbidity has still limited data. Objectives: to evaluate the prevalence of cardiovascular comorbidity in patients (pts) with PsA and PsO without arthritis in the dermatological hospital cohort. Methods: 592 pts (Male-348/Female-244) with moderate-to-severy plaque PsO, mean age 49.2±0.6 years, mean PsO duration 11.8±0.6 were included. PsO and PsA pts with cardiovascular disease (CVD), including coronary heart disease (CHD), arterial hypertension, (AH), atherosclerosis and cerebrovascular accident (CVA) were identify in the hospital Database reporting and coding by International Statistical Classification of Disease and Related Health Problems (ICD-10) between 2010 - 2011 years. M±m, t-test, (%) were calculated. All p<0.05 were considered to indicate statistical significance. Results: 220 out of 592 pts (37.2%) had PsA and 372 out of 592 pts (62.8%) had PsO alone. PsA pts were older then PsO pts – 53.3±0.9 and 46.9±0.9 (p<0.001). In PsA pts CVD coding as I 00 – I 99 were found in significantly more cases than in PsO pts – in 155 out of 220 pts (70.5%)/in 200 out of 372 pts (53.5%) accordingly (p<0.05). In PsA pts AH coding as I 10 - I 15 was found in significantly more cases than in PsO pts - in 138 out of 220 pts (62.7%) and in 178 out of 372 pts (47.9%) accordingly (p<0.001). In PsA pts CVA coding as I 65 – I 66 found significantly often than in PsO pts - in 48 out of 220 pts (22%) and in 57 out of 372 pts (15.3%) accordingly (p<0.05). CHD and Atherosclerosis coding as I 70 were registered significantly often in PsA pts compared to PsO pts – in 40 out of 220 pts (18%) and in 35 out of 372 pts (9.3%) accordingly (p<0.001). Conclusions: Cardiovascular comorbidity is common for PsA and PsO without arthritis pts. High frequency of CVD in PsA than PsO could be due to share inflammation pathways with atherosclerosis and age. Screening and accurate management of CVD risk factors in both diseases are needed. Disclosure of Interest: None declared